Changes in bone microarchitecture following kidney transplantation—Beyond bone mineral density. Issue 9 (2nd August 2018) - Sharma, Ashish K.; Toussaint, Nigel D.; Elder, Grahame J.; Rajapakse, Chamith S.; Holt, Stephen G.; Baldock, Paul; Robertson, Patricia L.; Ebeling, Peter R.; Sorci, Olivia R.; Masterson, Rosemary
Abstract: Bone disease in kidney transplant recipients (KTRs) is characterized by bone mineral density (BMD) loss but bone microarchitecture changes are poorly defined. In this prospective cohort study, we evaluated bone microarchitecture using non‐invasive imaging modalities; high‐resolution magnetic resonance imaging (MRI), peripheral quantitative computed tomography (pQCT), dual energy X‐ray absorptiometry (DXA), and the trabecular bone score (TBS) following kidney transplantation. Eleven KTRs (48.3 ± 11.2 years) underwent MRI (tibia), pQCT (radius) and DXA at baseline and 12 months post–transplantation. Transiliac bone biopsies, performed at transplantation, showed 70% of patients with high/normal bone turnover. Compared with baseline, 12‐month MRI showed deterioration in indices of trabecular network integrity—surface to curve ratio (S/C; −15%, P  =   0.03) and erosion index (EI; +19%, P  =   0.01). However, cortical area increased (+10.3%, P  =   0.04), with a non‐significant increase in cortical thickness (CtTh; +7.8%, P  =   0.06). At 12 months, parathyroid hormone values (median 10.7 pmol/L) correlated with improved S/C ( r  = 0.75, P  =   0.009) and EI ( r  = −0.71, P  =   0.01) while osteocalcin correlated with CtTh ( r  = 0.72, P  =   0.02) and area ( r  = 0.70, P  =   0.02). TBS decreased from baseline (−5.1%, P  =   0.01) with no significant changes in BMD or pQCT. These findings highlight a post–transplant deterioration in trabecular bone quality detected by MRI and TBS, independent of changes in BMD, underlining the potential utility of these modalities in evaluating bone microarchitecture in KTRs.